Convergence rate of the Levenberg-Marquardt method under Hölderian local error bound. (3rd July 2020) - Wang, Haiyan; Fan, Jinyan
ABSTRACT: In this paper, we study the convergence rate of the Levenberg-Marquardt (LM) method under the Hölderian local error bound condition and the Hölderian continuity of the Jacobian, which are more general than the local error bound condition and the Lipschitz continuity of the Jacobian. Various choices of the LM parameter are also discussed.